Analisis Penjatuhan Hukuman dalam Tindak Pidana Aborsi di Pengadilan Negeri Makassar : Studi Putusan Nomor:1224/Pid.Sus/2022/PN.Mks - Wahid Ramadhan; Andi Rahmah; Andi Tanwir Mappanyukki (Majelis: Jurnal Hukum Indonesia, 2025)
Abortion is prohibited under the Indonesian criminal law system. In fact, it is categorized as a crime against life, regulated by several laws and regulations, including the Criminal Code and the Health Law. Indonesian criminal law defines abortion as "Termination of Pregnancy," which is regulated by Articles 299, 346, 347, 348, and 349 of the Criminal Code. These articles clearly and unequivocally prohibit abortion for any reason, including abortion for emergency (forced) reasons, such as rape. This type of research is normative legal research (normative legal research method). The normative legal research method is a library legal research conducted by examining legal literature materials such as Legislation, Judge's Decisions, Books, Journals, Theses and Legal Dictionaries. The results of the study indicate that (1) The Judge imposed a sentence of 2 (two) years. This seems light and unfair because the defendant's actions should have been given a heavier sentence as stated in the case that the defendant had committed his crimes seven times. (2) The judge's considerations in imposing criminal sanctions in Decision Number 1224/Pid.Sus/PN.Mks, concluded that the judge's decision to sentence the defendant to two years in prison was lenient and did not reflect the sense of justice that should have been upheld. This was because the defendant's actions were classified as a serious crime that had a widespread moral and social impact on society.